TIDAL FLUCTUATIONS IN A LEAKY CONFINED AQUIFER: LOCALISED EFFECTS OF AN OVERLYING PHREATIC AQUIFER - Li L.; Jeng D.S.; Barry D.A. (My University, 2002)
Damping of tidal head fluctuations in a leaky confined coastal aquifer is enhanced by leakage into an overlying phreatic aquifer. We show that the phreatic aquifer is, however, resistant to the leakage flow and in particular, a deep phreatic aquifer can reduce the leakage effects significantly. An analytical solution, based on a vertical flow model for the phreatic aquifer, is derived for quantifying the role of this upper free water body in tidal propagation in the lower semi-confined aquifer.
Keywords: SEMI-CONFINED AQUIFER; PHREATIC AQUIFER; TIDAL FLUCTUATIONS; LEAKAGE